Studies on the Epidemiology of Postoperative Infection of Clean Operative Wounds - William R. Culbertson; William A. Altemeier; Luis Llanes González; E. O. Hill (1961)
Culbertson, W. R. M.D.; Altemeier, W. A. M.D.; GONZALEZ, LUIS L. M.D.; Hill, E. O. PH.D. Author Information